Optical solitons to the Kundu-Mukherjee-Naskar equation in (2+1)-dimensional form via two analytical techniques - Zafar, Asim; Raheel, M.; Ali, Khalid K.; İnç, Mustafa; Qaisar, Anoosha (Aip Publishing, 2022)
The current research is about the optical solitons of the Kundu-Mukherjee-Naskar (KMN) equation that are obtained by implementing the two proficient approaches named: the extended Jacobi's elliptic expansion function method and the exp(a) function method. The aforesaid methods are used for the first time in the KMN equation to obtain novel soliton solutions in terms of Jacobi's elliptic function solutions, which turn into dark, bright, and periodic solutions later. Also, the rational function solutions of the above-mentioned equation are obtained. The obtained solutions are also graphed and verified with the use of symbolic soft computations. The obtained results may be applied to illustrate the substantial concept of the studious structures as well as other related nonlinear physical structures.
Keywords: Kundu-Mukherjee-Naskar equation; extended Jacobi elliptic expansion function method; exp(a) function method; optical solitons